Improving Students’ Engagement in Listening Activities through Edpuzzle - Setiawati, Sari; Yuliana, Yohanes Gatot Sutapa; Ikhsanudin, Ikhsanudin (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
Students’ engagement is crucial for the success of listening activities, especially at the junior high school level. This study aimed to enhance students’ engagement in English listening activities using EDpuzzle, focusing on eighth-grade A students at SMP Islam Al-Azhar 17 Pontianak. Conducted over two cycles with 20 participants, the study addressed issues like distractions, disengagement, difficulty understanding audio, and feelings of frustration. The research employed a Classroom Action Research (CAR) design, involving two cycles of planning, action, observation, and reflection. Instruments used included observation checklists, tests, and field notes. Qualitative analysis showed a marked increase in engagement during the second cycle, after introducing EDpuzzle Station Challenge activities. EDpuzzle’s interactive features—visually engaging content, embedded questions, and the option to rewatch videos—made the listening experience more accessible and enjoyable. This boosted cognitive, behavioral, and emotional engagement, leading to better attendance, active participation, and fewer disruptions. Descriptive statistics revealed notable improvements, with 86.67% of students showing higher emotional engagement, 78.33% displaying increased cognitive engagement, and 86.67% showing improved behavioral engagement. Additionally, 85% of students scored above the success threshold in listening comprehension tests, particularly in identifying degrees of comparison and summarizing video content. In conclusion, EDpuzzle enhanced students’ engagement by creating a more interactive and enjoyable learning environment.